101k views
2 votes
jane and jill were simplifying the expression (2x2+x) +2(-x2+×) and obtained different answers . who is right and why?​

User Kayti
by
5.5k points

1 Answer

5 votes

Answer: who ever arrives at the answer x=0/3 =0 is correct

Explanation:

Even though I need supporting details from the individual answers of Jane and Jill to pass my own judgment.

Given the expression

(2x²+x) +2(-x²+×)=0

Let's us open the bracket

2x²+x-2x²+2x=0

Collecting like terms

2x²-2x²+x+2x=0

3x=0

x=0/3

x=0

User Ravi Kumar Gupta
by
5.1k points